An infant with large fontanelles, aplasia cutis congenita, tessier facial cleft, polydactyly inversus, and toe syndactyly: A previously undescribed syndrome?. (23rd February 2015) - Jackson, Jessica; Delk, Paula; Farrow, Emily; Griffith, Christopher; Lah, Melissa; Weaver, David D.
Abstract : We report on a 5‐month‐old female with large and widely spaced anterior and posterior fontanelles, aplasia cutis congenita, Tessier 3 oblique facial cleft, polydactyly, and syndactyly of toes. The polydactyly is unusual as an accessory finger is attached to the left fifth finger with mirrored, end‐to‐end fusion. We are naming this anomaly "polydactyly inversus." The infant appears to have a previously unreported syndrome of unknown cause. © 2015 Wiley Periodicals, Inc.